2021
DOI: 10.1186/s12889-021-10954-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes to body mass index, work self-efficacy, health-related quality of life, and work participation in people with obesity after vocational rehabilitation: a prospective observational study

Abstract: Background People on or at risk of sick leave from work due to obesity or obesity-related problems participated in a new vocational rehabilitation (VR). The study aimed to examine the outcome changes in the participants’ health-related quality of life (HRQoL), body mass index (BMI), return to work self-efficacy (RTWSE), work ability scale (WAS) and degree of work participation (DWP) after their participation in the 12-month VR programme. The secondary aim was to examine associations between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
(91 reference statements)
0
7
0
Order By: Relevance
“…Screening CA survivors for fatigue or related secondary problems at outpatient cardiology follow-up may identify those with rehabilitation needs and therefore potential future study participants. A multi-center trial including similar residential facilities in European countries 62,63 may increase pace of recruitment. The residential delivery method used by SCARF meant survivors need only attend twice, improving retention, but possibly reducing recruitment for survivors with work or caring commitments.…”
Section: Discussionmentioning
confidence: 99%
“…Screening CA survivors for fatigue or related secondary problems at outpatient cardiology follow-up may identify those with rehabilitation needs and therefore potential future study participants. A multi-center trial including similar residential facilities in European countries 62,63 may increase pace of recruitment. The residential delivery method used by SCARF meant survivors need only attend twice, improving retention, but possibly reducing recruitment for survivors with work or caring commitments.…”
Section: Discussionmentioning
confidence: 99%
“…However, changes in work participation can also depend on factors not directly affected by health or lifestyle changes, such as relations with managers and co-workers and other workplace factors. Workplace modifications can contribute to increased work ability as well as prevent sick leave (Franche & Krause, 2002 ; Kristman et al, 2020 ; Linge et al, 2021a , 2021b ; Schultz et al, 2007 ; Young et al, 2005 ), and job satisfaction has been shown to be an important factor for well-being at work (Ekberg & Ståhl, 2020 ; Figueredo et al, 2020 ; Hees et al, 2012 ; Linge et al, 2021b ; De Vries et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Until now, work focus has not been a part of lifestyle interventions for persons with obesity in Norway, although there is an increasing awareness of the problem of reduced work ability for this group (Linge et al, 2021a , 2021b ). In order to meet the challenges that persons living with obesity face regarding their working life, a newly developed work intervention was introduced as an additional element to a lifestyle intervention programme for persons with morbid obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Return to work (RTW) (ie return, maintain or stay at work) is often the outcome measure and the final goal; however, it explains only a small part of rehabilitation’s complex picture. 14 , 20 For employees, job satisfaction, mental function and work-home balance are important outcomes of the RTW process. 21 Previous research has indicated that people attending VR programmes may enhance work ability and reduce sick leave.…”
Section: Introductionmentioning
confidence: 99%
“…VR with a lifestyle intervention is new and unexplored. Only a few studies have focused on the association between multifactorial lifestyle risk and work ability 20 , 28 and factors that generate work participation for people with obesity. 29 By examining the work dimension’s interpretation, we can explore a more holistic picture of the complexity of obesity and work participation.…”
Section: Introductionmentioning
confidence: 99%